Gothic Opera in Britain and France: Genre, Nationalism, and Trans-Cultural Angst - Hoeveler, Diane; Cordova, Sarah (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
AbstractRescue operas developed along two somewhat different lines: “tyrant” operas and “humanitarian” operas within the general category of “opera semiseria,” or “opéra comique.” The first type corresponds to the conservative British “loyalty gothic,” with its focus on the trials and tribulations of the aristocracy, while the second type draws upon the Sentimental “virtue in distress” or “woman in jeopardy” genre, with its focus on middle class characters or women as the captured or besieged. The first category emphasized political injustice or abstract questions of law and embodied the threat of tyranny in an evil man who imprisons unjustly a noble character. Etienne Méhul’s Euphrosine and H.-M. Berton’s Les rigueurs du cloître (both 1790) are typical examples of the genre. “Humanitarian” operas, on the other hand, do not depict a tyrant, but instead portray an individual—usually a woman or a worthy bourgeois—who sacrifices everything in order to correct an injustice or to obtain some person’s freedom. Dalayrac’s Raoul, Sire de Créqui (1789) or Bouilly’s and Cherubini’s Les deux journées (1800) are examples, along with Sedaine’s pre-1789 works. But why, we might ask, were gothic dramas quickly transformed into gothic operas or what are known now as “rescue operas”? This essay examines the social and political ideologies that are explicit in the major gothic operatic adaptations of the most popular gothic novels of Britain, while at the same time examining British opera’s very close connections with French models as well as French adaptations of British cultural works.